Penerapan Latihan sasaran Target Kearah Gawang Terhadap Akurasi Shooting Dalam Permainan Sepakbola Di Club Old Star U-17 Lubuklinggau - Herista, Riki; Mulyono, Dr Dodik; M,P.d, Helvi Darsi (Jurnal MensSana, 2024)
This study aims to determine the shooting accuracy of Club Old Star U-17 players after applying target target training. This research method uses quantitative methods of quasi-experimental approach with pre-test and post-test designs. The population in this study was 20 Club Old Star U-17 players. Sampling is carried out by purposive sampling, which is a determination technique with certain considerations. The sample taken in this study was football players at Club Old Star U-17 in Lubuklinggau city totaling 20 people. The test given in this study by giving 2 tests, before and after treatment, descriptive statistics showed that the mean pre test (121) was smaller than the post test (147.5). This means that the average child has an increase in shooting accuracy scores. This improvement is possible because the approach used is very supportive of the child's condition. The results of the hypothesis test showed that there was a positive and significant effect of target training towards the goal on shooting accuracy in Club All Star U-17 Lubuklinggau athletes. Based on the analysis of hypothesis testing, it was found that tcount (7.465) > ttable (1.729), this means that Ho is rejected and Ha is accepted. In other words, the hypothesis proposed in this study can be accepted as correct, so it can be concluded that target training towards the goal can improve the shooting accuracy of Lubuklinggau U-17 old star players.